Pengabdian Kepada Masyarakat Pemasangan Paving Block TPA Al-Huda Desa Amawang Kanan - Elva Shanty Widuri; Fitriansyah; Arifin; Ahmad Riduan; Misnawati; Trie Rezky Novianti; Vanness Jan Ho Antony Djong (CV. SINAR HOWUHOWU, 2025)
Sustainable rural infrastructure development plays a crucial role in improving the quality of life, particularly in supporting religious education facilities. This community service program was carried out at Taman Pendidikan Al-Qur’an (TPA) Al-Huda in Amawang Kanan Village with the main objective of enhancing accessibility and environmental comfort through the installation of paving blocks. The method employed was a participatory and collaborative approach based on local needs, actively involving community members in planning, implementation, and evaluation stages. The results demonstrate that the paving block installation significantly improved the safety, cleanliness, and functionality of the TPA environment, especially during the rainy season. Beyond physical improvements, this program also fostered public awareness regarding the importance of environmentally friendly and sustainable infrastructure. The initiative exemplifies how the integration of technical, social, and educational approaches can effectively address local infrastructure issues while strengthening synergy between academia and the community.